2010
DOI: 10.1007/s00240-010-0321-2
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous nephrolithotomy for complex caliceal and staghorn stones in patients with solitary kidney

Abstract: Treatment of patients with solitary kidney having complex stones is one of the most challenging problem in urology. We present our experience with percutaneous nephrolithotomy (PCNL) in treating 16 patients with staghorn stones in a solitary kidney to determine long-term renal functional results. We retrospectively reviewed the records of 16 patients with complex caliceal or staghorn stones in a solitary kidney treated with PCNL. Demographic data, number and location of accesses, hemoglobin values, stone analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 23 publications
0
14
1
Order By: Relevance
“…We established 18-Fr mini tracts with the aim to decrease tract-related hemorrhage when multiple tracts were needed. The hemoglobin drop after PCNL was 3.5 ± 0.6 g/dl, and the transfusion rate was 13% in the PCNL monotherapy group in the present study, which was consist with other series, where the hemoglobin drop after PCNL ranged from 0.8 to 5.2 g/dl and the transfusion rate was 18.75% [10]. …”
Section: Discussionmentioning
confidence: 78%
“…We established 18-Fr mini tracts with the aim to decrease tract-related hemorrhage when multiple tracts were needed. The hemoglobin drop after PCNL was 3.5 ± 0.6 g/dl, and the transfusion rate was 13% in the PCNL monotherapy group in the present study, which was consist with other series, where the hemoglobin drop after PCNL ranged from 0.8 to 5.2 g/dl and the transfusion rate was 18.75% [10]. …”
Section: Discussionmentioning
confidence: 78%
“…Berkan et al (14) observed staghorn stones in 16 patients. The number of patients with hypertension before PCNL was fi ve and by the end of follow-up there was no new onset hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…Today, it is the treatment of choice for large-volume stone disease with the advantages of better stone clearance, costeVectiveness, and early convalescence as compared with other modalities like SWL or open surgery. An untreated kidney stone can damage the kidney; especially, struvite stones can destroy the kidney and cause life-threatening sepsis [4]. Studies have repeatedly demonstrated the safety and eYcacy of this minimally invasive technique, maintaining acceptable stone-free and symptom-free results, while minimizing associated complications [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%